Toward an Understanding of What Works in Professional Development for Online Instructors: The Case of PBS Teacherline - Storandt, Barbara C.; Dossin, Lia C.; Lacher, Anna Piacentini (Online Learning, 2012)
Research conducted in various settings suggests that preparation and support for online instructors should be considered separately from efforts to prepare face-to-face instructors. However, very few studies outline the ways in which preparation to teach online should differ, and only a handful link these practices to measurable outcomes that help define what is meant by effective. PBS TeacherLine’s professional development model presents an opportunity to examine a comprehensive, well-established effort that has undergone regular refinements over the past 11 years. Results from the yearlong study presented in this paper showed that PBS TeacherLine’s professional development model contributes positively to instructor satisfaction, retention, high quality online instruction, increased instructor reflection, and learner outcomes such as an overall positive course experience. These findings reveal promising best practices for online faculty professional development that are specific to the online environment.